Using Trichoderma asperellum to Antagonize Lasiodiplodia theobromae Causing Stem-End Rot Disease on Pomelo (Citrus maxima) - Nguyen Quoc Khuong; Dinh Bich Nhien; Le Thi My Thu; Nguyen Duc Trong; Phan Chan Hiep; Vo Minh Thuan; Le Thanh Quang; Le Vinh Thuc; Do Thi Xuan (Journal of Fungi, 2023)
Stem-end rot disease has been causing damage to the production of pomelos in Vietnam. The cur-rent study aimed to (i) isolate fungal pathogens causing pomelo stem-end rot disease (PSERD) and (ii) discover Trichoderma spp. that had an antagonistic ability against pathogens under in vitro conditions. Fungi causing PSERD were isolated from pomelo fruits with symptoms of stem-end rot disease and collected from pomelo farms in Ben Tre province, Vietnam. Moreover, 50 fungal strains of Trichoderma spp. also originated from soils of these pomelo farms in Ben Tre province and were dual-tested with the fungal pathogen on the PDA medium. The results demonstrated that 11 pathogenic fungi causing PSERD were isolated from the fruit and showed mycelial growth of roughly 5.33–8.77 cm diameter at 72 h after inoculation. The two fungi that exhibited the fast-est growth, namely, S-P06 and S-P07, were selected. ITS sequencing of the S-P06 and S-P07 fungi resulted in Lasiodiplodia theobromae. All the 50 Trichoderma spp. strains were allowed to antago-nize against the S-P06 and S-P07 strains under in vitro conditions. The greatest antagonistic effi-ciency was found in Trichoderma spp. T-SP19 at 85.4–86.2% and T-SP32 at 84.7–85.4%. The two antagonists were identified as Trichoderma asperellum T-SP19 and T-SP32. The selected strains of Trichoderma asperellum were potent as a biological control for fruit plants.